Control and analysis in the processing of dilis bagoong - Colinayo, Geronimo Ponciano ([s.n.], 1973)
An instructional material on the control and processing of dilis bagoong was constructed. More specifically, the study aimed to emphasize the need of quality control for the standardization of good products. The study showed how a 2:7 ratio by mass of salt and dilis the proper sterilization and time of processing gave the required pH concentration. Procedures used in the NIST laboratory were modified and apparatus for the analyses of total solids, NaCl, and protein content is devised to make it possible for secondary school students to improvise their own in the school shop or in their homes.